Pentingnya Sertifikasi Haji Untuk Kualitas Pembimbing Haji - Retno Wulandari (Jurusan Manajemen Dakwah, Fakultas Ilmu Dakwah dan Ilmu Komunikasi, UIN Syarif Hidayatulla, 2021)
AbstractThe writing of this scientific article is intended to explain the importance of Hajj certification for the quality of the Hajj guide. To find out the importance of certification and quality what happens if the Hajj advisor approves.Certification is one of the points in determining the level of professionalism of a person and the assessment of the competence of pilgrims is expected to provide positive energy and the best guidance for pilgrims.Hajj Guidance is a person in the field of Hajj who masters the knowledge of Hajj rituals who have participated in the activities of controlling Hajj and Umrah guides and assigned to guide the pilgrims. To become a guide, the pilgrim must master various competencies and languages and be required to be professional and responsible so as not to question the quality.The quality of conformity with various requirements that have met the requirements to support the need to meet the needs, with the needs made totality formed good quality. Quality Hajj guides are Hajj guides who have received certification and have Hajj certificates.Keywords: Certification, Hajj Guidance, Quality